Origin and palaeoenvironmental indications of Eocene to Oligocene primary lacustrine dolomite, Northern Tianshan Mountains, NW China. (15th August 2020) - Wang, Yizhe; Wu, Chaodong; Fang, Yanan; Ma, Jian; Shen, Bing; Huang, Fang; Zhou, Tianqi; Wang, Jialin; Zhang, Wei
Graphical abstract: Highlights: Dolostone deposited at 25–50 °C by Mg isotope Rayleigh distillation model. During the Eocene to Oligocene, the detrital zircon ages of 40–44 Ma was first found. Volcanic ash provided the Mg 2+ and high temperature for dolomite formation. The Anjihaihe dolostone are typical of naturally occurring primary dolostone. Abstract: During the Eocene to Oligocene, lacustrine dolostone developed in the Anjihaihe Formation on the northern margin of the Tianshan Mountains in the southern Junggar Basin. Dolostone formation is usually restricted to specific environmental and geochemical conditions; therefore, dolostone contains considerable information on palaeoenvironment and palaeoclimate changes. Furthermore, this dolostone provides more information on the formation process and formation mechanisms of dolostone. The studied dolostone is white to greyish white and consists of dolomite crystals that are 3–10 µm in size, homogeneous, subhedral to euhedral and nearly stoichiometric (with average Mg/Ca molar ratios of 0.97). The high Sr content (average 1996 ppm), relatively high δ 18 O values (average −1.8‰) and co-occurrence with halite and gypsum reflect evaporative and saline conditions. The δ 26 Mg values of the dolostone range from −0.81 to −2.44‰, with a mean of −1.78‰. Strong positive correlations exist between the δ 26 Mg values and depth (r = 0.76) and the Mg isotope Rayleigh distillation model results, which indicates that δ 26 Mg fractionation occurred in conjunction with evaporation and that most of the Anjihaihe lacustrine dolomite developed in a natural environment at 25–50 °C. Moreover, evidence of microbes can be found covering the surface of the dolostone in the presence of a few framboids of pyrite. Additionally, clay layers in the dolostone are primarily composed of bentonite (40–60%) but also contain small amounts of montmorillonite (0.8–3.5%) and zeolite (0.1–0.5%). Detrital zircon ages of 40–44 Ma are presented for the first time for the Anjihaihe Formation. The results show that understanding the primary lacustrine dolostone is significant and essential to reconstructing the evolution of palaeoenvironments and synsedimentary volcanic activity in the northern Tianshan Mountains during the Eocene to Oligocene. This work also provides a possible model that explains the formation of the studied dolostone in an evaporative saline lacustrine environment.